2005
DOI: 10.1093/beheco/arj032
|View full text |Cite
|
Sign up to set email alerts
|

Predator detection and avoidance by starlings under differing scenarios of predation risk

Abstract: Practically all animals must find food while avoiding predators. An individual's perception of predation risk may depend on many factors, such as distance to refuge and group size, but it is unclear whether individuals respond to different factors in a similar manner. We tested whether flocks of foraging starlings responded in the same way to an increased perception of predation risk by assessing three factors: (1) neighbor distances, (2) habitat obstruction, and (3) recent exposure to a predator. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 48 publications
6
80
1
2
Order By: Relevance
“…Buckingham & Peach 2006, Siriwardena et al 2007. Recent experimental research has also shown that seed-eating birds alter their foraging behaviour in response to vegetation manipulation (Devereux et al 2006, Whittingham et al 2006a) and the perceived predation risk has been suggested as a key factor explaining why granivorous birds prefer areas with greater visibility for foraging and feeding on the ground. Our results do not depart from this pattern because the occurrence of Blue Chaffinches in less sheltered locations (TC < 38%) was influence by the availability of pine seeds on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Buckingham & Peach 2006, Siriwardena et al 2007. Recent experimental research has also shown that seed-eating birds alter their foraging behaviour in response to vegetation manipulation (Devereux et al 2006, Whittingham et al 2006a) and the perceived predation risk has been suggested as a key factor explaining why granivorous birds prefer areas with greater visibility for foraging and feeding on the ground. Our results do not depart from this pattern because the occurrence of Blue Chaffinches in less sheltered locations (TC < 38%) was influence by the availability of pine seeds on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Further, an important factor influencing the speed of predator detection is habitat structure (Whittingham et al 2004;Devereux et al 2006). In our case, the advantage is clearly with the falcons--open salinas, no escape routes or shelter, and foraging singly are all disadvantageous to the waders.…”
Section: Discussionmentioning
confidence: 99%
“…A greater visual acuity would result in the detection of threats at a greater distance. The presence of visual obstacles in the local environment, like vegetation cover or rocks, can also reduce the ability to detect a threat at a given distance (Arenz and Leger, 1997;Devereux et al, 2006;Lima and Zollner, 1996).…”
Section: Submodelsmentioning
confidence: 99%
“…Predator presence is a well-known factor leading to longer scans in birds and mammals (Dacier et al, 2005;Devereux et al, 2006;Glück, 1987;Li et al, 2009;Mathot et al, 2009) although there are exceptions (Jones et al, 2007;Lima, 1992). Scan duration is also known to increase when animals are disturbed by people (Dyck and Baydack, 2004).…”
Section: Probability Of Predator Presencementioning
confidence: 99%
See 1 more Smart Citation